2013
DOI: 10.1111/myc.12062
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium keratitis in South India: causative agents, their antifungal susceptibilities and a rapid identification method for the Fusarium solani species complex

Abstract: Seventy Fusarium isolates derived from human keratomycosis were identified based on partial sequences of the β-tubulin (β-TUB) and translation elongation factor 1α (EF-1α) genes. Most of the isolates were confirmed as members of the F. solani species complex (75.71%), followed by the F. dimerum species complex (8.57%), the F. fujikuroi species complex (8.57%), the F. oxysporum species complex (4.29%) and the F. incarnatum-equiseti species complex (2.86%). A combined phylogenetic tree was estimated including al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
7
45
1
Order By: Relevance
“…In the present study, the common aetiological agents of corneal ulcers were identified as filamentous fungi rather than bacteria. Similar results were obtained by Bharathi et al [6], Manikandan et al [24] and Homa et al [15] in South India. Leck et al [22] also reported similar results from South, North and East India.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the common aetiological agents of corneal ulcers were identified as filamentous fungi rather than bacteria. Similar results were obtained by Bharathi et al [6], Manikandan et al [24] and Homa et al [15] in South India. Leck et al [22] also reported similar results from South, North and East India.…”
Section: Resultssupporting
confidence: 93%
“…In immunocompetent persons, Fusarium usually causes localized infections (Bourgeois et al 2010; De Pinho et al 2012; Calcaterra et al 2013; Homa et al 2013). Conversely, immunocompromised hosts, mainly those with acute onco-hematological diseases or after allogeneic hematopoietic stem cell transplant, have high risk of invasive life-threatening diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to in vitro testing, antifungal susceptibility profiles have been shown to vary between Fusarium species (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Correct identification to the species or species complex level may thus be crucial for patient treatment, although no in vitro-in vivo correlations have been demonstrated, and treatment is dependent on the type of infection (27).…”
mentioning
confidence: 99%